Identity-Based Political Preferences In The Elections (Study Of Manggarai Ethnicity In The 2012 And 2017 Kupang City Elections) - SYAFRUDDIN, Akhmad; KEON, Yohanes Fisher; NAMI, Yohanes Jimmy (International Journal of Environmental, Sustainability, and Social Science, 2023)
This research aims to explain the phenomenon of identity politics in the context of Regional Head Elections (Pilkada) in the scheme of the relationship between ethnicity and voters' political preferences in Pilkada contestations. The case raised in this research is the Kupang City Pilkada during the last two periods which included the pair Yonas Salean and Dr. Herman Man in the 2012-2017 period and the couple Jefri Riwu Kore and Dr. Herman Man in the 2017-2022 period. Interestingly, the two democratic contestation celebrations were won by the Mayor candidate who was paired with Dr. Herman Man. This fact gave rise to a number of assumptions that placed the figure of Dr. Herman Man as the determining factor for victory. This research specifically wants to measure whether identity politics has changed the behavior of choosing the Manggarai ethnic group in providing support to Dr Herman Man. To get an overview and answers, this research uses a qualitative approach with a case study type on the Manggarai ethnic group in Kupang City. Data collection techniques through interviews and documentation. The research results show that support for the Kupang Mayor candidate pair who collaborated with the Deputy Mayor candidate pair from the Manggarai ethnic group was strengthened by the presence of a unifying forum, namely Panga and IKMR as the basis for the Manggarai people's association in Kupang City. The existence of non-formal institutions is an effective consolidation medium for gathering support and strengthening internal ethnic solidity.